Transformational Leadership, Communication, and Work Motivation: Its Influence on Employee Performance at the Prodia Mataram Clinical Laboratory - Vidya Trisnawati; Ike Kusdyah Rachmawati; Yunus Handoko (Universitas KH. Abdul Chalim Mojokerto, 2025)
Prodia Clinical Laboratory, as one of the health service companies that continues to grow, Prodia faces the challenge of being able to continue to improve employee performance to support service innovation, especially during increasingly competitive Health industry competition. Transformational leadership, effective communication, and high work motivation are believed to have a role in improving optimal employee performance. The purpose of this study was to see how much the analysis of the influence of transformational leadership on employee performance, communication on employee performance, work motivation on employee performance, and transformational leadership, communication, and work motivation on employee performance. This study uses a quantitative approach to organic employees of the Prodia Mataram Clinical Laboratory. The research sample was 34 respondents using purposive sampling techniques. Statistical analysis techniques using SPSS. The test instruments used were validity and reliability tests, classical assumption tests, multiple regression analysis, hypothesis tests (T tests), and simultaneous tests (F tests). The results of the study show that 1) transformational leadership partially has a positive and significant effect on employee performance 2) communication partially has a positive and significant effect on employee performance 3) Work motivation partially has a positive and significant effect on employee performance 4) transformational leadership, communication and work motivation simultaneously have a positive and significant effect on employee performance.